2015
DOI: 10.2209/tdcpublication.56.131
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization-induced Intracellular Free Calcium Concentration Increases Show No Desensitizing Effect in Rat Odontoblasts

Abstract: Odontoblasts play an important role in the transduction of the sensory signals underlying dentinal pain. Transmembrane voltage-independent Ca(2+) influx in odontoblasts has been well described. Voltage-dependent Ca(2+) influx has also been reported, but its biophysical properties remain unclear. The aim of the present study was to investigate the desensitizing effect of voltage-dependent Ca(2+) influx in rat odontoblasts by measuring depolarization-induced intracellular free Ca(2+) concentrations ([Ca(2+) ]i )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…In conclusion, we showed that odontoblasts expressed slow activating voltage-dependent K + currents that are carried by Kv1.1, 1.2, and/or 1.6. Previous reports have shown various Ca 2+ influx/mobilization pathways are mediated by mechano-sensing cation channels, store-operated Ca 2+ channels (SOCs), as well as depolarization-induced Ca 2+ entry (Shibukawa and Suzuki, 2003 ; Son et al, 2009 ; Tsumura et al, 2010 , 2013 ; Kojima et al, 2015 ; Shibukawa et al, 2015 ). Cellular deformation in odontoblasts, which might be elicited by dentinal fluid movement following dentin stimulation, also activates Ca 2+ influx and leads to depolarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we showed that odontoblasts expressed slow activating voltage-dependent K + currents that are carried by Kv1.1, 1.2, and/or 1.6. Previous reports have shown various Ca 2+ influx/mobilization pathways are mediated by mechano-sensing cation channels, store-operated Ca 2+ channels (SOCs), as well as depolarization-induced Ca 2+ entry (Shibukawa and Suzuki, 2003 ; Son et al, 2009 ; Tsumura et al, 2010 , 2013 ; Kojima et al, 2015 ; Shibukawa et al, 2015 ). Cellular deformation in odontoblasts, which might be elicited by dentinal fluid movement following dentin stimulation, also activates Ca 2+ influx and leads to depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these mechanosensitive ionic channels, as well as ionotropic and metabotropic receptors, increases intracellular free Ca 2+ concentrations, leading to plasma membrane depolarization. Membrane depolarization in odontoblasts is known to activate K + conductance; however, the detailed properties of this process remains to be clarified (Kojima et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%